Addams family - Sonnenfeld, Barry; Rudin, Scott, 1958-; Thompson, Caroline, 1956-; Wilson, Larry, 1948-; Huston, Anjelica; Julia, Raul; Lloyd, Christopher, 1938-; Wilson, Elizabeth, 1921-2015; Ricci, Christina; Malina, Judith, 1926-2015; Hedaya, Dan; Struycken, Carel; et al. (Hollywood, Calif Paramount Home Video, 1999)
When long-lost Uncle Fester reappears after twenty-five years in the Bermuda Triangle, the other members of the off-beat Addams clan plan a great celebration, only to begin to suspect that he may not be who he claims to be.
Widescreen version enhanced for 16x9.
Based on characters created by Charles Addams.
Originally released as a motion picture in 1991.
Director of photography, Owen Roizman ; production designed by Richard MacDonald ; editor, Dede Allen ; costumes designed by Ruth Myers ; music, Marc Shaiman.
Anjelica Huston, Raul Julia, Christopher Lloyd, Elizabeth Wilson, Christina Ricci, Judith Malina, Dan Hedaya, Carel Struycken, Paul Benedict, Christopher Hart, Dana Ivey, Jimmy Workman.
MPAA rating: PG-13.
Keywords: Addams family (Fictitious characters) -- Drama; DVD-Video discs; Films for the hearing impaired; Video (DVD); Video recordings for the hearing impaired; Film adaptations; Fiction films; Comedy films; Drama; Feature films